Astonishing 35S rDNA diversity in the gymnosperm species Cycas revoluta Thunb - Wang, Wencai (Chromosoma, 2015)
In all eukaryotes, the highly repeated 35S ribosomal DNA (rDNA) sequences encoding 18S-5.8S-26S ribosomal RNA (rRNA) typically show high levels of intragenomic uniformity due to homogenisation processes, leading to concerted evolution of 35S rDNA repeats. Here, we compared 35S rDNA divergence in several seed plants using next generation sequencing and a range of molecular and cytogenetic approaches. Most species showed similar 35S rDNA homogeneity indicating concerted evolution. However, Cycas revoluta exhibits an extraordinary diversity of rDNA repeats (nucleotide sequence divergence of different copies averaging 12 %), influencing both the coding and non-coding rDNA regions nearly equally. In contrast, its rRNA transcriptome was highly homogeneous suggesting that only a minority of genes (<20 %) encode functional rRNA. The most common SNPs were C > T substitutions located in symmetrical CG and CHG contexts which were also highly methylated. Both functional genes and pseudogenes appear to cluster on chromosomes. The extraordinary high levels of 35S rDNA diversity in C. revoluta, and probably other species of cycads, indicate that the frequency of repeat homogenisation has been much lower in this lineage, compared with all other land plant lineages studied. This has led to the accumulation of methylation-driven mutations and pseudogenisation. Potentially, the reduced homology between paralogs prevented their elimination by homologous recombination, resulting in long-term retention of rDNA pseudogenes in the genome. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00412-015-0556-3) contains supplementary material, which is available to authorized users.